Quasi-Experimental Investigation of Nutritional Interventions and Cognitive Advancement in Stunted Children - Dewi Anggriani Harahap; Fitri Apriyanti; Syukrianti Syahda; Armiyati Nur; Mustika Hana Harahap (Postgraduate, University of Mataram, 2025)
Childhood nutrition is essential for optimum growth and cognitive development, particularly in populations with a significant incidence of stunting. This research used a longitudinal cohort design to evaluate the effects of nutritional treatments on children's growth and cognitive development. A quasi-experimental design was used to compare children who underwent structured nutrition treatments—micronutrient supplementation, dietary variety enhancement, and maternal nutrition education—with those who did not receive the interventions. A total of 128 children, aged 6 months to 6 years, were recruited using stratified random selection and observed at various time intervals. The study findings indicated a significant reduction in stunting rates within the intervention group (from 35% to 20%) in contrast to the control group, which saw just a marginal decline (to 32%). Cognitive assessments using the Bayley Scales of Infant Development (BSID) and the Wechsler Preschool and Primary Scale of Intelligence (WPPSI) indicated superior results in the intervention group (p < 0.05). Socioeconomic variables, notably maternal education and family income, impact the intervention's efficacy, highlighting the need for a comprehensive strategy that merges nutritional assistance with educational initiatives for mothers. This research underscores the need of comprehensive, evidence-based dietary policy to enhance children's growth and cognitive development.